Rancang Bangun Sistem Rekap Nilai Mahasiswa Prodi Jaringan Telekomunikasi Digital Politeknik Negeri Malang Menggunakan Jaringan Fiber Optik Berbasis Website Jurusan Teknik Elektro, Program Studi Jaringan Telekomunikasi Digital, Politeknik Negeri Malang - Yudhistira Hendra Wijaya; M. Nanak Zakaria; Yoyok Heru Prasetyo Isnomo (Jurnal Jaringan Telekomunikasi, 2021)
In undergoing the lecture process, one of the important elements is the student and the student's value. In the study program of Digital Telecommunication Network, Malang State Polytechnic itself is currently still using the data processing systems of student grades on standard computer worksheets without any special software. In addition, the increasing data from year to year will make it difficult in the process of access and search, where at this time Information technology is required to be faster and more accessible. In this study the method used in the student value recap is by creating a website. Then the website is uploaded on the server and uses fiber optic transmission media. The results of testing the system's website functionality could run according to planning. In testing the performance of website using wireless transmission media and optical fiber produced the best value of delay, packet loss, and throughput when using optical fiber networks, with 0.113s delay results for wireless transmission media and 0.004s with transmission media using optical fiber at 9 users accessing the website simultaneously. For the throughput value obtained was 48.229 kbps with wireless transmission media and 956.347 kbps with fiber optic transmission media. From this results, the more number of users obtained, the better the delay and throughput. And the packet loss parameters obtained 10.457% with wireless transmission media and 0.667% with optical fiber transmission media when accessed by 9 users